Meyerson’s phenomenon around warty epidermal nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
Meyerson’s phenomenon is called a usually eczematous dermatitis arising around any skin lesion; on the other hand, we talk about Meyerson’s nevus when the eczematous reaction occurs around a melanocytic nevus. In 2011, 17 cases of Meyersons phenomenon had been described around skin lesions of various types, especially seborrheic warts in the literature (2); 3 cases of Meyerson phenomenon around sebaceous nevus of the scalp, caused at least in two cases by perilesional atopic dermatitis, had also been reported (1). However, Meyerson’s phenomenon around a linear warty epidermal nevus has never been so far described. A dermatitis, as in our case, located only around a pre-existing lesion, can be hardly classified. Its classification is or becomes much easier when it is also present in other locations at the time of the diagnosis of Meyerson phenomenon or it appears later as in our case.